2020
DOI: 10.1029/2020je006416
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Latitudinal Short‐Scale Gravity Field of Jupiter Using Slepian Functions

Abstract: Early gravity measurements performed by the Juno spacecraft determined Jupiter's low‐degree gravity harmonics, including the first estimate of the planet's north‐south asymmetric field. The retrieved information was used to infer that the strong zonal winds visible at the cloud tops must extend down a few thousand kilometers, where they are suppressed in the deep interior. The next frontier for the Juno gravity experiment includes, among other goals, the determination of Jupiter's small‐scale gravity field wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We found the same features for the gravitational and tidal field of Jupiter, showing further details of the Juno gravity experiment. We demonstrated that Orbit14 is able to provide an independent estimation of the dynamical parameters of Jupiter, working in parallel with other research groups which employ the NASA OD software MONTE (Iess et al, 2018;Parisi et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We found the same features for the gravitational and tidal field of Jupiter, showing further details of the Juno gravity experiment. We demonstrated that Orbit14 is able to provide an independent estimation of the dynamical parameters of Jupiter, working in parallel with other research groups which employ the NASA OD software MONTE (Iess et al, 2018;Parisi et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…For the future experiments with a larger amount of data, some aspects need to be further investigated. First of all, it will be important to see if the remaining signals at the closest approaches will increase in magnitude and if random accelerations will be able to still absorb them or other models related to physical processes will be required (see Durante et al 2017;Parisi et al 2020). Moreover, the use of a satellite-dependent formulation of the tides on Jupiter will be essential to confirm possible deviations of the tidal parameters of Jupiter from their static values (see Notaro et al 2019).…”
Section: Experiments With Orbit14mentioning
confidence: 99%
“…The high correlations between zonal harmonics beyond degree 10 due to the uneven spatial resolution prevent the estimation of the gravity moments with the required accuracy. A similar effect was investigated with the Juno gravity experiment, which sought to circumvent this limitation by either adopting a different mathematical base than spherical harmonics or setting constraints on the surface gravity from realistic physical considerations (Galanti et al 2017;Parisi et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The gap between the Canberra and Madrid data is due to the rising and setting times of the stations (handover), as well as the limit set on the elevation angle. All simulated Doppler data from all arcs are combined into a multiarc solution for the solved-for parameters (Parisi et al 2020(Parisi et al , 2021.…”
Section: Trajectory and Doppler Tracking Simulations For Gravity Scie...mentioning
confidence: 99%
“…Each simulation event is contained in an arc of 24 hr duration, centered about the 8 hr ring pass of continuous tracking. The range-rate residuals from all arcs are combined in a multiarc square-root information filter for the estimation of parameters of interest (Durante et al 2020;Parisi et al 2020). The simulation setup allows for the estimation of parameters that are independent for each arc, called local in Table 2.…”
Section: Estimation Processmentioning
confidence: 99%